"Leadership matters?" : finding voice, connection and meaning in the 21st century - Mabey, Christopher, 1951-; Knights, David, 1940- (Routledge studies in leadership research, 2018)
"In recent years we have seen what could be described as a moral meltdown in the corporate corridors of power. Few sectors have escaped high profile scandals, with public officials and leaders guilty of malpractice, duplicity, fraud and corporate malfeasance. Conventional leadership theories appear to be inadequate to equip those with power to act ethically and responsibly. At a more macro level, many of the social and environmental problems we face in the 21st century could in fact, be described as spiritual in nature, rooted in a flawed human condition. Leadership Matters brings together an eclectic mix of authors of different faith traditions, to explore what this spiritual and cultural transformation might look like. For too long we have relied on external codes of conduct, which are, at best, blunt instruments for creating ethical practice. So, chapter by chapter, this book examines our interior lives from the perspective of mind, body and soul. The unashamed premise of this book is that true and influential leadership comes from the inside with each chapter presenting what it means to lead respectfully, critically, responsibly and humbly in the gritty reality of the twenty first century workplace. This volume will be of keen interest to academics and practitioners in the field of leadership and the related disciplines."--Provided by publisher